Monitoring the 'Monitor': A Critique of Krashen's Five Hypotheses (Dhaka University Journal of Linguistics, 2011)
This article discusses Krashen's Monitor Model and the attendant five hypotheses. Since its 1977 publication, Krashen, through a series of revisions, have tried to explain the way learners acquire a second language. This article closely looks at his basic premises and the criticism they have generated to better understand both the Monitor Model and its various lacunae and biases.Key words: Affective Filter; Krashen; Language Acquisition Device (LAD); Monitor Model; Second Language Acquisition (SLA).DOI: 10.3329/dujl.v2i4.6903Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.139-146